Mga mungkahing gawain at pagsasanay sa mabisang pagtuturo ng pakahulugan ng mga salita sa ikaapat na baitang ng mababang paaralan - Ilagan, Josefina Gonzales 1923- (s.n.], 1971)
This seminar paper attempts to present different techniques in teaching connotative meanings of words. Each technique contains explanations and exercises that will develop the teacher's skill and ability to prepare instructional materials slanted towards the linguistics approach in teaching vocabulary. The suggested exercises will develop the pupil's skill in understanding different connotative meanings of words presented in various context. Each technique is followed by a lesson plan to show how such an activity can be carried out effectively in classroom situations.